2003
DOI: 10.1097/01.jcp.0000095349.32154.a5
|View full text |Cite
|
Sign up to set email alerts
|

GABA and Schizophrenia: A Review of Basic Science and Clinical Studies

Abstract: Alterations in the GABA neurotransmitter system are found in clinical and basic neuroscience schizophrenia studies as well as animal models and may be involved in the pathophysiology of schizophrenia. The interaction of GABA with other well-characterized neurotransmitter abnormalities remains to be understood. Future studies should elucidate the potential therapeutic role for GABA ligands in schizophrenia treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
148
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(158 citation statements)
references
References 212 publications
2
148
1
1
Order By: Relevance
“…[47][48][49] The current study has presented several lines of evidence for the specific involvement of GABA A receptor subunit genes located in the 5q schizophrenia risk locus. We detected association between schizophrenia and both GABRA1 and GABRP in a patient sample of Portuguese descent.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…[47][48][49] The current study has presented several lines of evidence for the specific involvement of GABA A receptor subunit genes located in the 5q schizophrenia risk locus. We detected association between schizophrenia and both GABRA1 and GABRP in a patient sample of Portuguese descent.…”
Section: Discussionmentioning
confidence: 72%
“…42 The 5q GABA genes are plausible candidates for the schizophrenia risk gene in the 5q locus based on a converging body of literature implicating GABA system dysfunction in schizophrenia pathophysiology. [43][44][45][46][47][48][49] In schizophrenia patient brain samples, markers of GABAergic neurons are reduced in expression and postsynaptic receptor complexes are increased in number. 47,50,51 Furthermore, there is evidence that neuregulin 1 (NRG1) and dysbindin (DTNBP1), two schizophrenia candidate risk genes, 33,[52][53][54][55][56][57][58][59][60][61][62][63][64][65] interact with the GABA A receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantive evidence of impaired GABA neurotransmission in SCZ (Wassef et al, 2003), no previous study has directly associated GABGR3 to the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal glutamatergic signaling has been a prominent 'hypothesis' about the pathophysiology of schizophrenia, 29,30 and it has been suggested that a number of the genes currently implicated in schizophrenia are related to NMDA (N-methyl-D-aspartate) signaling in the brain. [31][32][33] An equally prominent hypothesis involves gamma-aminobutyric acid (GABA) neuronal function, [34][35][36][37] but this avenue has been relatively unexplored from a genetic perspective. The recent demonstration that loss of NRG1/ERBB4 signaling alters the tangential migration of cortical interneurons and reduces the number of GABAergic interneurons in post-natal cortex 38 is potentially a quite important mechanistic lead, since statistical evidence suggests that these two genes may synergistically increase the risk for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%